The relationship between leadership personality traits and the accuracy of performance of some scouting skills among female students of the College of Physical Education and Sports Sciences at the University of Sulaimani - Ahmed, Shaker Mahmoud (Sulaimani Journal for Humanities, 2026)
This research aimed to identify the level of scouting skills among female students at the College of Physical Education and Sports Sciences, University of Sulaimani, and to analyze the relationship between personal leadership traits and the performance of these skills. The researcher adopted a descriptive approach with a correlational method, as it was suitable for the nature of the research problem. The study sample consisted of (32) female students from the third year at the College of Physical Education and Sports Sciences, University of Sulaimani, during the 2023–2024 academic year. They were selected purposively. The researcher used a variety of tools and devices to measure the leadership traits and scouting skills under investigation (square knot, diagonal turn, tent pitching). Data were collected using precise methodological methods, and the results were analyzed using the SPSS statistical software. The results showed statistically significant differences between some personal leadership traits and the scouting skills under study among the third-year students, indicating a correlation between the two. Based on the results, the researcher recommends the importance of enhancing the psychological aspects and scouting skills of the students through structured training programs aimed at continuously and systematically developing these aspects.
Keywords: Leadership personal traits; scouting skills